The Development of Problem-Based Learning in English Language Education Through Academic Literature - Uzma, Fauziyatul; Sulistyaningrum, Siti Drivoka; Dewanti, Ratna (Institut Agama Islam Negeri (IAIN) Curup, 2025)
With this study, the authors explore the evolution of Problem-Based Learning (PBL) in English language education and its substantial contribution to language proficiency, critical thinking, and student engagement. With technology evolving at a fast pace and world becoming a global village, the conventional means of education are slowly dying and are not enough to prepare students for the challenges of the 21st century. In response to these challenges, Project-Based Learning (PBL) has mature as a student-centered approach that promotes relevant and real-world problems and tasks, active learning, and collaboration. The corresponding research brings together research published from 1980 through 2024, emphasizing the period of 2019–2024. Employing thematic analysis, three main themes emerged from the literature, which were language proficiency, developing critical thinking skills, challenges in implementing PBL, and technological integration. The research shows that PBL leads to higher levels of language proficiency, especially in speaking and writing, promotes critical thinking, and increases engagement among learners. However, many barriers exist, including lack of teacher preparation and limited curriculum and materials availability. Finally, the paper concludes that the potential of PBL in English language education is maximized with teacher training, curricular flexibility, and equitable access to technology.